Method for preparing polyvinyl polyamide composite reverse osmosis membrane by coupling lignosulfonate through reverse phase interfacial polymerization
During the production process of the reverse osmosis membrane, the lignin sulfonate is combined with the polyvinyl substrate by using the reverse phase interface polymerization method to form a crosslinked structure, which solves the problem of difficult balance of the reverse osmosis membrane flux and retention rate in the prior art, and achieves efficient and low-cost reverse osmosis membrane preparation.
Patent Information
- Application Number
- CN202510401188.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2025-06-27
AI Technical Summary
Existing reverse osmosis membranes are difficult to find a balance between improving water flux and salt retention, and traditional manufacturing processes are complex and costly.
The reverse phase interfacial polymerization method is used to combine lignin sulfonate with polyvinyl substrate to form a crosslinked structure, breaking the "trade-off" effect of flux and retention, and preparing a polyvinyl polyamide composite reverse osmosis membrane.
High water flux (up to 2.2Lm-2h-1·bar-1) and high interception (up to 98.93%) of the reverse osmosis membrane were achieved, while reducing production costs.
Smart Images

Figure CN120204954A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water treatment membranes, and particularly to a polyvinyl polyamide composite reverse osmosis membrane and its preparation. Background Art
[0002] The total amount of fresh water resources on the earth is very small, and most of it is seawater. Seawater accounts for 97.47% of the total water volume, and only 2.53% is fresh water. Today, with relatively scarce water resources, seawater desalination, as an effective means to solve the shortage of fresh water resources, has received extensive attention from local coastal governments and large water-consuming enterprises represented by petrochemical, electric power, and steel industries. Reverse Osmosis (RO) is a separation operation that uses a pressure difference as the driving force to separate the solvent from the solution. The reverse osmosis technology is the most widely used seawater desalination process and also the seawater desalination technology with the lowest energy cost so far.
[0003] Forming a thin composite structure by preparing a polyamide (PA) separation layer through interfacial polymerization (IP) on a porous substrate membrane is an important technical process for preparing reverse osmosis membranes. Breaking the "trade-off" effect and finding a balance between high permeability and excellent desalination selectivity is the key to designing efficient reverse osmosis membranes. Traditional reverse osmosis substrate membranes mostly use polysulfone, polyethersulfone, etc. Their manufacturing processes are complex and the costs are relatively high, resulting in high prices for the prepared reverse osmosis membranes. The thickness of the polyethylene lithium-ion battery separator is 5 μm, and the average pore size is 10 - 70 nm. Replacing the traditional polyester non-woven fabric and polysulfone ultrafiltration layer with thinner polyethylene can greatly reduce the production cost of reverse osmosis membranes. However, due to the poor hydrophilicity of the polyethylene substrate, the initially added aqueous phase cannot spread using the traditional interfacial polymerization method. Using substrate surface treatment or surfactant aqueous phase can make it spread, but the steps are complex and the cost is high, and the obtained polyamide separation layer has low rejection. In addition, due to the large and uneven pore size of the substrate, a high-flux and high-rejection reverse osmosis membrane cannot be obtained using the direct reverse interfacial polymerization method.
[0004] Lignin is a natural renewable polyphenol polymer with extremely high content in nature. Its storage volume ranks second to that of wood fiber. It has outstanding advantages such as wide source, low price and biodegradability. As one of the lignin derivatives, lignin sulfonate has a basic structure of phenylpropane derivatives. Lignin sulfonate contains a large number of sulfonate groups in its molecules, which gives it hydrophilicity. At the same time, there are a large number of active functional groups, such as phenolic hydroxyl, alcoholic hydroxyl and carboxylmethyl. The oxygen atoms and sulfur atoms in these functional groups contain unbonded electron pairs, which can participate in interfacial polymerization reactions to form cross-linked structures, providing the possibility of breaking the "trade-off" effect of reverse osmosis membrane flux and salt retention. However, lignin sulfonate has not been directly added to the preparation process of polyethylene reverse osmosis membrane. The traditional method of directly adding lignin sulfonate to the aqueous phase solution of polysulfone-based membrane cannot effectively improve the water flux or retention rate of reverse osmosis membrane. The present invention creatively combines lignin sulfonate and reverse phase interfacial polymerization, and combines a post-treatment step, so that the obtained polyethylene-based composite polyamide reverse osmosis membrane has both high water flux and high selectivity. Summary of the invention
[0005] In view of the prior art, in order to prepare a reverse osmosis membrane with high permeability and high selectivity, the present invention provides a method for preparing a polyethylene polyamide composite reverse osmosis membrane by reverse phase interfacial polymerization coupling lignin sulfonate. In order to achieve the above purpose, the present invention adopts the following technical scheme:
[0006] A method for preparing a polyethylene-polyamide composite reverse osmosis membrane by coupling lignin sulfonate through reverse phase interfacial polymerization, comprising a porous polyolefin substrate, an aromatic polyamide separation layer, and lignin sulfonate molecules contained in the polyamide separation layer, wherein the hydrophilic sulfonate groups and active functional groups such as phenolic hydroxyl groups, alcoholic hydroxyl groups, carboxylmethyl groups and sulfonic acid groups exist; the polyamide layer is composed of an organic phase containing aromatic polyacyl chloride monomers and an aqueous phase containing aromatic diamine monomer-based lignin sulfonate, and a cross-linked network is formed through reverse phase interfacial polymerization; the flux of the composite reverse osmosis membrane is >1.8Lm -2 h -1 bar -1 , salt rejection rate>98.0%.
[0007] Furthermore, a method for preparing a polyvinyl polyamide composite reverse osmosis membrane by coupling lignosulfonate through inverse interfacial polymerization. The lignosulfonate molecule contains many hydrophilic sulfonate groups and a large number of active functional groups, such as phenolic hydroxyl groups, alcoholic hydroxyl groups, and carboxymethyl groups, etc. There are also a large number of active functional groups, such as phenolic hydroxyl groups, alcoholic hydroxyl groups, and carboxymethyl groups, etc. The oxygen atoms, sulfur atoms, etc. in such functional groups contain unshared electron pairs and can participate in the interfacial polymerization reaction to form a cross-linked structure, providing the possibility to break the "trade-off" effect between the flux and salt rejection of the reverse osmosis membrane. The flux of the composite reverse osmosis membrane can reach 2.2 Lm -2 h -1 ·bar -1 , and the salt rejection rate can reach 98.93%.
[0008] A method for preparing a polyvinyl polyamide composite reverse osmosis membrane by coupling lignosulfonate through inverse interfacial polymerization, comprising the following steps:
[0009] (1) Dissolve the aromatic polyacyl chloride monomer in an organic phase solution and stir it thoroughly by ultrasonic waves to obtain an organic phase aromatic polyacyl chloride solution;
[0010] (2) Contact the organic phase aromatic polyacyl chloride solution in step (1) with one side of the polyethylene substrate membrane for 1 - 15 min, and pour off the excess organic phase aromatic polyacyl chloride solution;
[0011] (3) Dissolve the amine monomer, lignosulfonate, and camphorsulfonic acid in deionized water and stir it thoroughly to obtain an aqueous solution, and adjust the aqueous solution to pH 8 - 11 to obtain the adjusted aqueous solution;
[0012] (4) Pour the adjusted aqueous solution prepared in step (3) onto the organic phase aromatic polyacyl chloride solution in step (2), contact for 1 - 15 min, carry out an interfacial polymerization reaction to form a film, and pour off the excess aqueous solution;
[0013] (5) Dry the film obtained in step (4);
[0014] (6) Immerse the film obtained in step (5) in an alcohol solution to obtain a polyvinyl polyamide composite reverse osmosis membrane, and then store it in deionized water.
[0015] Preferably:
[0016] In step (1), the aromatic polyacyl chloride monomer is one or a combination of several of isophthaloyl chloride, terephthaloyl chloride, phthaloyl chloride, trimesoyl chloride, polyaromatic sulfonyl chloride, etc.;
[0017] The solvent of the organic phase solution is one or a combination of several of n - hexane, cyclohexane, toluene, benzene, ethyl acetate, dodecane.
[0018] In the step (1), the mass concentration of the aromatic polyacyl chloride monomer in the organic phase aromatic polyacyl chloride solution is 0.01-0.3 wt%.
[0019] In the step (3), the amine monomer is one or a combination of m-phenylenediamine, o-phenylenediamine, p-phenylenediamine, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, o-benzidine, 1,2-propanediamine, 1,3-propanediamine, 2,4-diaminotoluene, 4,5-dichloro-o-phenylenediamine, and melamine;
[0020] The lignosulfonate is one or a combination of sodium lignosulfonate, calcium lignosulfonate, ammonium lignosulfonate, magnesium lignosulfonate, and sulfonated sulfate lignin.
[0021] In the step (3), the mass fraction of the amine monomer in the aqueous solution is 0.1-10 wt%;
[0022] The mass fraction of the lignosulfonate in the aqueous solution is 0.1-10 wt%;
[0023] The mass fraction of camphorsulfonic acid in the aqueous solution is 0.2-20 wt%.
[0024] In the step (3), the aqueous solution is adjusted to pH 8-11 by adding triethylamine.
[0025] In the step (5), the drying condition is: heat treatment at 40-120 °C for 5-30 min.
[0026] In the step (6), the alcohol in the alcohol solution is one or a combination of isopropyl alcohol, absolute methanol, benzyl alcohol, 1,2-propanediol, 1,3-propanediol, ethylene glycol, N-methylpyrrolidone, dimethyl sulfoxide, and N,N-dimethylformamide.
[0027] In the step (6), the film obtained in the step (5) is immersed in the alcohol solution for 1-120 min.
[0028] The described polyvinyl polyamide composite reverse osmosis membrane comprises:
[0029] A porous polyolefin substrate;
[0030] An aromatic polyamide separation layer formed on the porous polyolefin substrate by reverse interfacial polymerization;
[0031] The described aromatic polyamide separation layer is a crosslinked network formed by reverse interfacial polymerization of an organic phase containing an aromatic polyacyl chloride monomer and an aqueous phase containing an aromatic diamine monomer and a lignosulfonate.
[0032] The traditional composite polyamide reverse osmosis membrane uses a two-layer structure of polyester non-woven fabric and polysulfone ultrafiltration layer as the support layer, which is now replaced by a single-layer polyethylene lithium-ion battery separator in the present invention, greatly reducing the manufacturing cost of the reverse osmosis membrane. At the same time, the project adopts the reverse interfacial polymerization method, first adding an oil phase containing polyacyl chloride, and then adding an aqueous phase containing amine monomers and lignosulfonate. The lignosulfonate molecule contains more sulfonate groups, endowing it with hydrophilicity. At the same time, there are a large number of active functional groups, such as phenolic hydroxyl groups, alcoholic hydroxyl groups, and carboxymethyl groups. The oxygen atoms, sulfur atoms, etc. in such functional groups contain unshared electron pairs and can participate in the interfacial polymerization reaction to form a cross-linked structure, breaking the "trade-off" effect between the reverse osmosis membrane flux and salt rejection, and obtaining a high-flux and high-rejection polyvinyl polyamide reverse osmosis membrane. The raw materials of the polyethylene base used in the present invention are low in price, and the preparation process avoids the surface modification of the bottom membrane and the addition of surfactants, greatly reducing the preparation cost. The product can be applied on a large scale in the fields of water treatment, seawater desalination, brackish water desalination, etc.
[0033] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0034] (1) In the present invention, a single-layer polyethylene lithium-ion battery separator is used to replace the two-layer structure of traditional polyester non-woven fabric and polysulfone ultrafiltration layer as the support layer, greatly reducing the manufacturing cost of the reverse osmosis membrane.
[0035] (2) In the present invention, by using lignosulfonate (sodium lignosulfonate, calcium lignosulfonate) as the second aqueous phase functional monomer to participate in the reverse interfacial polymerization process, the cross-linking and hydrophilic functions of lignosulfonate are exerted, while ensuring a high reverse osmosis membrane water flux (2.2Lm -2 h -1 ·bar -1 ), a high rejection rate (98.93%) of the reverse osmosis membrane is obtained. Description of the Drawings
[0036] Figure 1 is the process flow chart of the preparation of the polyvinyl polyamide composite reverse osmosis membrane;
[0037] Figure 2 is the scanning electron microscope image of the reverse osmosis membranes prepared in Comparative Example 1 and Example 3 of the present invention;
[0038] Figure 3 is the atomic force microscope image of the reverse osmosis membranes prepared in Comparative Examples 1-2 and Examples 1-4 of the present invention;
[0039] Figure 4 is the water contact angle image of the reverse osmosis membranes prepared in Comparative Examples 1-2 and Examples 1-4 of the present invention;
[0040] Figure 5It is a comparison chart of the water flux and rejection rate of the reverse osmosis membranes prepared in Comparative Examples 1-2 and Examples 1-4. Detailed implementation mode
[0041] The present invention will be further described below in conjunction with specific implementations. However, the present invention is not limited to the following embodiments. Without departing from the content and scope of the present invention, the changed examples should be included within the technical scope of the present invention.
[0042] The preparation environment for all reverse osmosis membranes in the examples is: temperature 25°C, humidity 45%, normal pressure.
[0043] The polyethylene lithium-ion battery separator used in the examples was purchased from Shanghai Enjie New Materials Technology Co., Ltd., with model numbers: HS16, SV9.
[0044] The performance test device for the reverse osmosis membranes prepared in the examples, experimental conditions: 20°C, 1.6 MPa, pre-pressurized for 1 h, 2000 ppm NaCl salt solution.
[0045] Comparative Example 1
[0046] (1) Prepare a hexane solution with a mass concentration of 0.2 wt% trimellitic acid chloride (TMC).
[0047] (2) First, immerse the polyethylene substrate film in the TMC organic phase solution for 4 min, remove the excess solution on the surface, and then air-dry.
[0048] (3) Dissolve m-phenylenediamine (MPD) with a mass concentration of 2.4 wt% and camphorsulfonic acid with a mass concentration of 4.8 wt% in water to obtain an aqueous phase solution, and add triethylamine to adjust the pH to 9.8.
[0049] (4) Immerse the film obtained in step (2) in the MPD aqueous phase solution for 6 min for interfacial polymerization, remove the excess solution on the surface, and then air-dry.
[0050] (5) Heat-treat the obtained film at 90°C for 10 min, soak the film in isopropanol for activation for 15 min, and then store it in deionized water to obtain a polyvinyl polyamide composite reverse osmosis membrane.
[0051] Analysis and testing were carried out on the polyvinyl polyamide composite reverse osmosis membrane prepared in Comparative Example 1:
[0052] Install the reverse osmosis membrane prepared in this example into the membrane performance test device, experimental conditions: 20°C, 1.6 MPa, pre-pressurized for 1 h, 2000 ppm NaCl salt solution; experimental results: water flux: 1.76 Lm -2 h -1 ·bar -1 , NaCl rejection rate: 97.7%.
[0053] Comparative Example 2
[0054] (1) Prepare a hexane solution of trimesoyl chloride (TMC) with a mass concentration of 0.2 wt%.
[0055] (2) First, immerse the polyethylene base film in the TMC organic phase solution for 4 min, remove the excess solution on the surface, and then air-dry it.
[0056] (3) Dissolve m-phenylenediamine (MPD) with a mass concentration of 2.4 wt%, camphorsulfonic acid with a mass concentration of 4.8 wt%, and lignin with a mass concentration of 1 wt% in water to obtain an aqueous phase solution, and add triethylamine to adjust the pH to 9.8.
[0057] (4) Immerse the film obtained in step (2) in the MPD aqueous phase solution for 6 min for interfacial polymerization, remove the excess solution on the surface, and then air-dry it.
[0058] (5) Heat-treat the obtained film at 90 °C for 10 min, soak the film in isopropanol for activation for 15 min, and then store it in deionized water to obtain a polyvinyl polyamide composite reverse osmosis membrane.
[0059] Analyze and test the polyvinyl polyamide composite reverse osmosis membrane prepared in Comparative Example 2:
[0060] Install the reverse osmosis membrane prepared in this example into a membrane performance test device. Experimental conditions: 20 °C, 1.6 MPa, pre-pressurize for 1 h, 2000 ppm NaCl salt solution; Experimental results: Water flux: 1.84 Lm -2 h -1 ·bar -1 , NaCl rejection rate: 97.4%.
[0061] Example 1
[0062] (1) Prepare a hexane solution of trimesoyl chloride (TMC) with a mass concentration of 0.2 wt%.
[0063] (2) First, immerse the polyethylene base film in the TMC organic phase solution for 4 min, remove the excess solution on the surface, and then air-dry it.
[0064] (3) Dissolve m-phenylenediamine (MPD) with a mass concentration of 2.4 wt%, camphorsulfonic acid with a mass concentration of 4.8 wt%, and sodium lignosulfonate with a mass concentration of 0.5 wt% in water to obtain an aqueous phase solution, and add triethylamine to adjust the pH to 9.8.
[0065] (4) Immerse the film obtained in step (2) in the MPD aqueous phase solution for 6 min for interfacial polymerization, remove the excess solution on the surface, and then air-dry it.
[0066] (5) The obtained membrane was heat-treated at 90 °C for 10 min, soaked in isopropanol for activation for 15 min, and then stored in deionized water to obtain a polyvinyl polyamide composite reverse osmosis membrane.
[0067] The polyvinyl polyamide composite reverse osmosis membrane prepared in Comparative Example 2 was analyzed and tested:
[0068] The reverse osmosis membrane prepared in this example was installed in a membrane performance test device. Experimental conditions: 20 °C, 1.6 MPa, pre-pressurized for 1 h, 2000 ppm NaCl salt solution; Experimental results: Water flux: 2.115 Lm -2 h -1 ·bar -1 , NaCl rejection rate: 98.46%.
[0069] Example 2
[0070] Referring to Example 1, the difference is that the mass concentration of sodium lignosulfonate added to the aqueous solution is 1 wt%.
[0071] The membrane performance test conditions were the same as those in Example 1. Test results: Water flux: 2.2 Lm -2 h -1 ·bar -1 , NaCl
[0072] rejection rate: 98.93%.
[0073] As Figure 2 shown by the scanning electron microscope results, at this time, the polyamide layer on the surface of the reverse osmosis membrane is denser, and its rejection rate is improved, which is related to the cross-linked network formed by reverse interfacial polymerization coupling with lignin; at the same time, as Figure 4 shown by the water contact angle test, since lignosulfonate contains a large number of hydrophilic groups, while improving the rejection rate of the reverse osmosis membrane, its hydrophilicity is improved, its water contact angle is smaller, and the water flux is increased, which also coincides with Figure 3 the surface roughness trend shown by the atomic force test.
[0074] Example 3
[0075] Referring to Example 1, the difference is that the mass concentration of sodium lignosulfonate added to the aqueous solution is 1.5 wt%
[0076] The membrane performance test conditions were the same as those in Example 1. Test results: Water flux: 1.88 Lm -2 h -1 ·bar -1 , NaCl rejection rate: 98.66%.
[0077] Example 4
[0078] Referring to Example 1, the difference is that the mass concentration of sodium lignosulfonate added to the aqueous solution is 2 wt%.
[0079] The membrane performance test conditions are the same as those in Example 1. Test results: water flux: 2.115 Lm -2 h -1 ·bar -1 , NaCl rejection rate: 98.7%.
[0080] A method for preparing a polyvinyl polyamide composite reverse osmosis membrane by coupling lignosulfonate through inverse interfacial polymerization according to the present invention uses a polyethylene lithium-ion battery separator, greatly reducing the cost of the reverse osmosis membrane. At the same time, by adding lignosulfonate to the aqueous solution, the performance of the reverse osmosis membrane can reach: water flux 2.2 Lm -2 h -1 ·bar -1 , rejection rate 98.93%, which is a preparation method for a low-cost and high-performance reverse osmosis membrane and has good application potential.
Claims
1. A method for preparing a polyethylene polyamide composite reverse osmosis membrane by reverse phase interfacial polymerization coupling lignin sulfonate, characterized in that: The following steps are involved: (1) dissolving an aromatic polyacyl chloride monomer in an organic phase solution and fully ultrasonically stirring the solution to obtain an organic phase aromatic polyacyl chloride solution; (2) contacting the organic phase aromatic polyacyl chloride solution in step (1) with one side of the polyethylene base film for 1 to 15 minutes, and discarding the excess organic phase aromatic polyacyl chloride solution; (3) dissolving the amine monomer, lignin sulfonate, and camphor sulfonic acid in deionized water and stirring the mixture to obtain an aqueous solution, and adjusting the pH of the aqueous solution to 8-11 to obtain an adjusted aqueous solution; (4) pouring the adjusted aqueous solution prepared in step (3) onto the organic aromatic polyacyl chloride solution in step (2) for 1 to 15 minutes to carry out interfacial polymerization reaction and form a film, and then pouring off the excess aqueous solution; (5) drying the film obtained in step (4); (6) Soaking the membrane obtained in step (5) in an alcohol solution to obtain a polyethylene polyamide composite reverse osmosis membrane, and then storing it in deionized water.
2. The method for preparing a polyethylene polyamide composite reverse osmosis membrane by reverse phase interfacial polymerization coupling lignin sulfonate according to claim 1, characterized in that: In step (1), the aromatic polyacyl chloride monomer is one or a combination of isophthaloyl chloride, terephthaloyl chloride, phthaloyl chloride, trimesoyl chloride, polyvalent aromatic sulfonyl chloride, etc.; The solvent of the organic phase solution is one or a combination of n-hexane, cyclohexane, toluene, benzene, ethyl acetate and dodecane.
3. The method for preparing a polyethylene polyamide composite reverse osmosis membrane by reverse phase interfacial polymerization coupling lignin sulfonate according to claim 1, characterized in that: In step (1), the mass concentration of the aromatic polyacyl chloride monomer in the organic phase aromatic polyacyl chloride solution is 0.01-0.3 wt %.
4. The method for preparing a polyethylene polyamide composite reverse osmosis membrane by reverse phase interfacial polymerization coupling lignin sulfonate according to claim 1, characterized in that: In step (3), the amine monomer is one or a combination of m-phenylenediamine, o-phenylenediamine, p-phenylenediamine, 4,4-diaminodiphenyl ether, 4,4-diaminodiphenylmethane, o-benzylamine, 1,2-propylenediamine, 1,3-propylenediamine, 2,4-diaminotoluene, 4,5-dichloro-o-phenylenediamine, and mesitylenetriamine; The lignin sulfonate is one or a combination of sodium lignin sulfonate, calcium lignin sulfonate, ammonium lignin sulfonate, magnesium lignin sulfonate, and sulfonated sulfate lignin.
5. The method for preparing a polyethylene polyamide composite reverse osmosis membrane by reverse phase interfacial polymerization coupling lignin sulfonate according to claim 1, characterized in that: In step (3), the mass fraction of the amine monomer in the aqueous solution is 0.1 to 10 wt %; The mass fraction of lignin sulfonate in the aqueous solution is 0.1-10wt%; The mass fraction of camphorsulfonic acid in the aqueous phase solution is 0.2-20wt%.
6. The method for preparing a polyethylene polyamide composite reverse osmosis membrane by reverse phase interfacial polymerization coupling lignin sulfonate according to claim 1, characterized in that: In step (3), the aqueous phase solution is adjusted to pH 8-11 by adding triethylamine.
7. The method for preparing a polyethylene polyamide composite reverse osmosis membrane by reverse phase interfacial polymerization coupling lignin sulfonate according to claim 1, characterized in that: In step (5), the drying conditions are: heat treatment at 40-120° C. for 5-30 min.
8. The method for preparing a polyethylene polyamide composite reverse osmosis membrane by reverse phase interfacial polymerization coupling lignin sulfonate according to claim 1, characterized in that: In step (6), the alcohol in the alcohol solution is one or a combination of isopropanol, anhydrous methanol, benzyl alcohol, 1,2-propylene glycol, 1,3-propylene glycol, ethylene glycol, N-methylpyrrolidone, dimethyl sulfoxide, and N,N-dimethylformamide.
9. The method for preparing a polyethylene polyamide composite reverse osmosis membrane by reverse phase interfacial polymerization coupling lignin sulfonate according to claim 1, characterized in that: In step (6), the membrane obtained in step (5) is immersed in an alcohol solution for 1 to 120 minutes.
10. The method for preparing a polyethylene polyamide composite reverse osmosis membrane by reverse phase interfacial polymerization coupling lignin sulfonate according to claim 1, characterized in that: In step (6), the polyvinyl polyamide composite reverse osmosis membrane comprises: Porous polyolefin substrate; generating an aromatic polyamide separation layer on the porous polyolefin substrate by reverse phase interfacial polymerization; The aromatic polyamide separation layer is a cross-linked network formed by reverse phase interfacial polymerization of an organic phase containing aromatic polyacyl chloride monomers and an aqueous phase containing aromatic amine monomers and lignin sulfonate.
Citation Information
Patent Citations
Preparation method of high-flux and high-interception nanofiltration membrane based on sodium lignin sulfonate
CN111437740A
Preparation method of reverse osmosis membrane
CN111974225A
Seawater desalination reverse osmosis composite membrane as well as preparation method and application thereof
CN117919946A
Preparation method of polyamide composite membrane using lignin to assist interfacial polymerization
CN118142363A
Application of sulfonated reverse osmosis membrane in silicon or silicon-aluminum pollution resistance
CN119015911A
Cited By
Reverse osmosis membrane and preparation method thereof
CN117244418A
Preparation method of lignin-modified high-flux polyamide composite membrane
CN120502251A